HIN9/468: The Last Mile - Secure and mobile data processing in healthcare - Bludau, HB; Vocke, A; Herzog, W (JMIR Publications, 1999)
MotivationAccording to the Federal Ministry the avowed target of modern medicine is to administer the best medical care, the newest scientific insights and the knowledge of experienced specialists on affordable conditions to every patient no matter whether he is located in a rural area or in a teaching hospital. One way of administer information is on mobile tools. To find out more about the influence of mobile computer on the physician-patient relation, the acceptance of these tools as well as prerequisites of new security and data-processing concepts were investigated in a simulation study. MethodsThe Personal Digital Assistant ResultsAfter the investigation week more than 2/3 of the participants indicated that they expect no or a positive modification of their communication behaviour. To emphasise is a group of test persons (one out of five), who feared a negative modification of their communication behaviour. Mobile data processing was judged as important and useful by more than two third of the professionals asked. ConclusionsAt present the original concept of a multifunctional device with integration of mobile voice and data communication did not prove as practicable. Rather a multi-device concept with stationary, mobile and hand-held device has to be developed.